The Specific Energy Absorption Of Local Wood Subjected To Quasi-Static Loading - SAID, MD RADZAI; Zakaria, Mohd Firdaus; Ismail, Mohd Khairi (2012)
An experimental investigation was carried out to study the specific energy absorbed of Malaysia local wood. Eleven species of wood were chosen which are, Nyatoh (Palaquim Obocatum), Merbau (Intsia Bijuga), Meranti Putih (Shorea Macroptera), Kelapa Sawit (Elais Guineensis), Kempas (Koompasia Malaaensis), Jati (Tectona Grandis), Cengal (Neobalanocarpus Heimii), Meranti Merah (Shorea Collina), Balau Cina (Shorea spp.), Balau Merah (Shorea spp.), and Kapur (Dryobalanops Aromatia). The experiment was performed in quasi-statically compression method using universal testing machine to obtain the material mechanical properties. Specimens were loaded in axial, circumferential and radial compression of local woods, the highest value of energy absorption and kink-band phenomena as well as its effect on energy absorption were determined and discussed in this paper.